Resolvin D1 and Resolvin E1 Promote the Resolution of Allergic Airway Inflammation via Shared and Distinct Molecular Counter-Regulatory Pathways - Levy, Bruce D. (Frontiers in Immunology, 2012)
Resolvins are generated from omega-3 fatty acids during inflammatory responses in the lung. These natural mediators interact with specific receptors to decrease lung inflammation and promote its resolution in healthy tissues. There are several lung diseases of chronic inflammation that fail to resolve, most notable asthma. This common disorder has a lifetime prevalence of nearly 10% and is characterized, in part, by chronic, non-resolving inflammation of the airway. Pro-resolving mediators are generated during asthma; however, their biosynthesis is decreased in severe and uncontrolled asthma, suggesting that the chronic, adaptive inflammation in asthmatic airways may result from a resolution defect. This article focuses on recent insights into the cellular and molecular mechanisms for resolvins that limit adaptive immune responses in healthy airways.